Experimental Studies on the Normal Impact of Fly Ash Particles with Planar Surfaces - Ming Dong; Sufen Li; Jun Xie; Jian Han (Energies, 2013)
This paper presents the results of a comprehensive program of experiments in which fly ash particles were impacted under controlled conditions against a flat steel surface. The overall aim of these experiments was to gain an understanding of the ash deposition process in a pulverized coal boiler system. A continuous nitrogen flow carrying fly ash particles was used to examine the effect of particle incident velocity and particle diameter (dp) on the normal restitution coefficient, and of the particle diameter on the critical velocity. The effect of the incident normal velocity and particle diameter on the normal restitution coefficient was also examined. The results show that the normal restitution coefficient increases rapidly with increasing incident velocity when this incident velocity is less than the yield velocity, and rapidly decreases with increasing incident velocity when the incident velocity is greater than the yield velocity. The critical velocity, determined solely by the first-contact energy loss, is proportional to dp−5/6 and therefore becomes larger for smaller particles. For instance, in the present work, the velocity vc of a particle with diameter of 85 μm is 0.19 m/s, which increases to 0.42 m/s for particles with a diameter of 65 μm.